Action Research – Reflective Teacher in Practice on the Basis of a System of Educating Students of Undergraduate Courses Leading toaA Master’s Degree in Great Britain - Kucińska, Estera (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
Classroom research about teaching and learning is essential part of teaching practice. Unfortunately very often it is under-estimated by teachers for many reasons. One of them is teachers difficulty in interpretation and practical use of the research. Understanding what happens when teachers and students meet in the classroom enable them to improve their teaching and learning processes. Without reflection on what should be improved or changed the whole process is incomplete and may have serious impact on students’ learning ability. Good classroom teacher must have understanding of what goes in the classroom and what matters in teaching from what does not. Good research creates the possibility for teacher to be reflective practitioner and explore implications of what good teacher and learners do in the classroom so all can benefit. Action research is designed to bridge the gap between practice and research. It combines diagnosis, action and reflection based on factors which influence teaching process and better its understanding. Action research which is perform according to its principles is the source of knowledge for both practitioners and academics.. Reflection is main factor of all stages of action research. The researcher who carries out such a research becomes participant and practitioner because he is part of educational reality which he researched.